TCML - an XML-based test case format - Jaafar, Mohd Farid; Selamat, Mohd Hasan; Abd Ghani, Abdul Azim (IEEE, 2006)
Testing is important and gives the confident to the developer and user; but it is expensive and may consume at least 50% of the total costs involved in developing software. This cost is just for a normal application but if it involves extreme and critical software, the number might increases. As we know, designing test suite for testing is a tedious and meticulous work. We need to have a deep understanding of the program before we could design a good test suite and even an expert tends to miss some test cases. Manual testing for large-scale program is very expensive and frustrating for humans. The same scenario applies in Visual Programming Language (VPL). Visual Programming (VP) is a much complex program than conventional one. Testing VP program give users the confidence on what they visualize is correctly transformed according to their perception. Most studies in designing test suites are using requirement specification, complex technique (i.e. Z) and third-party tools that require novices and non-expert user to supply information that is not familiar to them. It is certain that the information they supplied is more or less inaccurate and thus affects the test suite produced. Furthermore, there are no standard structures in exchanging the data about a program. The objective of this paper is to propose an XML-based test case language called Test Case Markup Language (TCML).